Design of VHF Directional Antenna on Class B Automatic Identification System (AIS) for Vessel Traffic Monitoring - Supriyanto, Eko; Hasan, Abu; Bramantyo, Hutama Arif; Nurrani, Hanny (Politeknik Negeri Semarang, 2023)
The majority of Automatic Identification System (AIS) equipment used on ships, harbormasters, and monitoring stations utilizes antennas that possess an omnidirectional beam pattern, covering all directions in a 360-degree range. One limitation inherent to omnidirectional antennas is their susceptibility to signal dispersion, resulting in suboptimal signal gain in certain directions. In the context of using omnidirectional antennas at Port AIS stations or other Monitoring Stations situated in expansive terrestrial regions, it is observed that the monitoring range is reduced. The objective of this study is to develop a prototype of a directional antenna capable of enhancing the monitoring range of ship traffic monitoring stations in alignment with the specific direction requested by land-based monitoring stations. The approach being utilized is the prototype method. This methodology encompasses the sequential steps of data collection, material and issue identification, planning, modeling, building, testing, and implementation.